Applications of Nonviral Biomaterials for microRNA Transfection in Bone Tissue Engineering - Zhu, Mengyao; Gu, Yingzhi; Bian, Ce; Xie, Xianju; Bai, Yuxing; Zhang, Ning (Frontiers in Materials, 2022)
Bone tissue engineering, which involves scaffolds, growth factors and cells, has been of great interest to treat bone defects in recent years. MicroRNAs (miRNAs or miRs) are small, single-stranded, noncoding RNAs that closely monitor and regulate the signaling pathway of osteoblast differentiation. Thus, the role of miRNAs in bone tissue engineering has attracted much attention. However, there are some problems when miRNAs are directly applied in the human body, including negative charge rejection of the cell membrane, nuclease degradation, immunotoxicity and neurotoxicity. Therefore, it is necessary to use a suitable carrier to transfect miRNAs into cells. In contrast to viral vectors, nonviral vectors are advantageous because they are less immunogenic and toxic; they can deliver miRNAs with a higher molecular weight; and they are easier to construct and modify. This article reviews the application of different miRNAs or anti-miRNAs in bone tissue engineering and the related signaling pathways when they promote osteogenic gene expression and osteogenic differentiation of target cells. An overview of the properties of different types of nonviral miRNA-transfected biomaterials, including calcium phosphates, nanosystems, liposomes, nucleic acids, silk-based biomaterials, cell-penetrating peptides, bioactive glass, PEI and exosomes is also provided. And the evaluations in load efficiency, release efficiency, cell uptake rate, biocompatibility, stability and biological immunity of nonviral miRNA-transfected biomaterials are given. This article also confirms that these biomaterials stably deliver miRNA to promote osteogenic gene expression, osteogenic differentiation of target cells and mineralization of the extracellular matrix. Because there are differences in the properties of various nonviral materials, future work will focus on identifying suitable transfection materials and improving the transfection efficiency and biocompatibility of materials.